Experimental Investigation of a New Design of Insulation Gypsum Plaster Blocks - Binti Katman H.Y.; Khai W.J.; Benjeddou O.; Mashaan N. (MDPI, 2023)
Green building materials are an alternative to ordinary materialsoffering multiple environmental benefits. This study consists of an experimental investigation of a new design of gypsum plaster blocks. First, a mix design of gypsum plaster and water mixture was prepared. The optimal mix composition was determined according to the mechanical and physical properties, such as the water absorption, the temperature of hydration, the density, and the compressive strength of different gypsum plaster and water mixtures made by varying the water dosage. The second part of this investigation aims to study a new design of green blocks prepared from the optimal water and gypsum plaster mixture. The new blocks are perforated to lighten them and to reduce their thermal conductivity in order to make them moreinsulate. Experimental tests were conducted on the block prototype, such as the measurement of dimensional tolerances, compressive strength, density, flatness, water absorption, residual moisture, surface hardness, and thermal conductivity. Experimental test results show that the new blocks have very low density, and their compressive strength is sufficient for wall construction. In addition, the manufacturing process of the new blocks is very easy and very fast. Finally, the obtained physical and mechanical properties of the new gypsum plaster blocks give it the opportunity to be used for interior walls for building constructions. 2022 by the authors.